Fingermark visualization exploiting electrostatic detection apparatus (ESDA): The effect of the composition and age of the latent deposit. Issue 3 (8th February 2021) - Zampa, Francesco; Mancini, Luca; Caligiore, Gaetano
Abstract: Paper evidence usually undergoes two consecutive examinations in forensic laboratories: ESDA (electrostatic detection apparatus) to detect indented impressions and a subsequent search for fingermarks by optical, physical, and chemical techniques. The ability of ESDA in visualizing fingermarks is well known. The aim of the present study is to understand better how long fingermarks can be developed with ESDA and if the different constituents of fingermarks show a different susceptibility to being developed. Several types of marks were collected from six donors on A4 standard office copy paper and tested with ESDA up to 69 days from deposition. A clear difference between natural, eccrine, and sebaceous marks emerged, being the latter ones better developed. ESDA developed standard sebaceous marks up to 16 days from deposition, whereas natural marks were visible within a few days. Eccrine marks were mainly visualized in reverse mode, despite the quality of these marks was not as good as the sebaceous marks. The appearance of the mark (standard/reverse) seemed to be correlated with time since deposition. Data suggest that the mechanism by which ESDA visualizes the fingermarks could be related to the residue (water‐soluble and/or non‐water‐soluble) available on the surface of the substrate and not yet absorbed by the paper. ESDA could act as a useful screening tool in fingermark visualization on porous surfaces, especially because it is a non‐destructive technique. Therefore, as a general procedure, it is highly recommended to acquire potential fingermarks developed by means of ESDA before proceeding with fingermark visualization.